2013
DOI: 10.1371/journal.pone.0068734
|View full text |Cite
|
Sign up to set email alerts
|

Yeast “Make-Accumulate-Consume” Life Strategy Evolved as a Multi-Step Process That Predates the Whole Genome Duplication

Abstract: When fruits ripen, microbial communities start a fierce competition for the freely available fruit sugars. Three yeast lineages, including baker’s yeast Saccharomyces cerevisiae, have independently developed the metabolic activity to convert simple sugars into ethanol even under fully aerobic conditions. This fermentation capacity, named Crabtree effect, reduces the cell-biomass production but provides in nature a tool to out-compete other microorganisms. Here, we analyzed over forty Saccharomycetaceae yeasts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
194
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(221 citation statements)
references
References 30 publications
(55 reference statements)
11
194
0
2
Order By: Relevance
“…It has previously been shown that Crabtree-positive yeast species show high glucose consumption rates 14. Here we show that the glucose uptake rates and ethanol production rates for all fermenting yeasts are equal to or higher than K. marxianus , which is the SCN yeast with the highest initial glucose uptake rate in our experiments.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…It has previously been shown that Crabtree-positive yeast species show high glucose consumption rates 14. Here we show that the glucose uptake rates and ethanol production rates for all fermenting yeasts are equal to or higher than K. marxianus , which is the SCN yeast with the highest initial glucose uptake rate in our experiments.…”
Section: Resultssupporting
confidence: 65%
“…K. lactis is short-term Crabtree-positive (present results), but long-term Crabtree-negative (Table1 and Fig. S7) 14. Other investigated yeast species that diverged from the rest of the Saccharomyces lineage prior to, or at approximately the same time as K. lactis , such as P. pastoris , D. vanrijiae , E. coryli and K. marxianus , are both short- and long-term Crabtree-negative 14.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…This suggests that Saccharomyces yeasts are the most dominant alcoholic fermentation microorganisms [75][76][77]. Even in the presence of oxygen, S. cerevisiae, is the predominant yeast species responsible for the production of ethanol [78,79]. The production of ethanol, toxic to other microbes, has been hypothesized to be a niche defense mechanism for S. cerevisiae [42].…”
Section: Yeastsmentioning
confidence: 99%